Study of alternative geometry of hollow self-compacting concrete masonry blocks - Bortoletto, M. [UNESP]; Albuquerque, M. C.F. [UNESP]; Spósito, F. A.; Silva, R. G. [UNESP] (My University, 2020)
To evaluate the geometrical influence of new types of hollow concrete blocks, six different geometries were investigated using self-consolidating concrete to fabricate the blocks. The cell shapes studied were circular, hexagonal and rectangular comprising a total of six different net areas. Mechanical tests of the blocks and masonry prisms constructed using the blocks were performed, as well as a finite element analysis of the thermal resistance of the blocks. The fresh and hardened properties of self-compacting concrete were evaluated. The results showed that the cell shapes influenced the block compressive strength capacity. The block with the circular cell had the highest axial compressive strength. Prisms with circular and hexagonal cells had higher axial compressive strength than the prisms with rectangular cells. Larger longitudinal wall thicknesses of blocks provided a greater capacity to absorb deformations, except for the blocks with rectangular cells, which had low strength and deformation capacity. The linear relationship between the increase in cell area as a function of inner temperature caused a reduction of heat transfer in the inner and outer surfaces as the cell area increased. In general, this study demonstrated that the cell geometry influenced the investigated properties, but also showed the possibility of manufacturing blocks using self-consolidating concrete.
Keywords: Compressive strength; Concrete blocks; Geometry; Heat transfer; Self-compacting concrete